Orosomucoid 1 promotes epirubicin resistance in breast cancer by upregulating the expression of matrix metalloproteinases 2 and 9 - Luo Qiong (Taylor & Francis Group, 2021)
Orosomucoid 1 (ORM1) has been shown to be upregulated in the serum of breast cancer patients; however, the expression and function of ORM1 in breast cancer remains unknown. We measured the expression of ORM1 in breast cancer tissues and cell lines using qRT-PCR. A colony formation assay was done to assess cell proliferation and Transwell and wound healing assays were performed to determine the migration and invasion capacity of the cells, respectively. In addition, a CCK-8 assay was used to measure epirubicin cytotoxicity and western blot assays were done to analyze the putative mechanisms of epirubicin sensitivity. We found that the expression of ORM1 was upregulated in breast cancer tissues and cell lines. The expression of ORM1 enhanced the proliferation and migration of the cell lines. In contrast, down-regulation of ORM1 inhibited the expression of MMP-2 and MMP-9 and activation of the AKT/ERK signaling pathway. Therefore, ORM1 may represent a potential therapeutic target for breast cancer and promote epirubicin resistance by regulating the expression of MMP-2 and MMP-9, as well as activating the AKT/ERK signaling pathway.